RESTRUCTURING AND REDESIGNING THE PESANTREN TOWARD AN EFFECTIVE EDUCATIONAL INSTITUTION - Yayan Rahayani (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2017)
Abstract Pesantren is an Islamic boarding school and is the oldest community-based education system in Indonesia. The methods of instruction in Pesantren are over 400 years. The focus of Pesantren is Islamic teaching, teaching community values, literacy and numeracy. Pesantren has to compete with the contemporary educational practices currently used in Indonesia. Pesantren, as an educational institution faces challenges not only come from outside, but also from within the organization. The complex roles of the Kyai as the leader, for instance, needs to be revisited and this paper highlights the history, key roles of the Kyai and the institutional framework of Pesantren. Arguably, there is a need to challenge the role of the leaders (Kyai) and communication patterns within the Pesantren it can respond to contemporary issues influencing education in Indonesia. The study suggests the use of restructuring and redesigning for Pesantren. The restructuring includes, but not limited to, transforming leadership role and involving teachers in designing the curriculum. Redesigning encompasses the idea of shared responsibility among teachers and redesigning infrastructure. In short, Pesantren has embedded strengths and resources used to face challenges and accommodate changes in society. The Kyai have significant roles in revisiting those resources. Abstrak Pesantren merupakan sistem pendidikan agama Islam berbasis masyarakat yang tertua di Indonesia. Metodologi pengajaran di pesantran bahkan sudah dikenal selama kurang lebih 400 tahun. Diantara ajaran utama pesantren adalah memberikan pengajaran tentang agama Islam, nilai-nilai luhur dalam masyarakat, selain ilmu baca tulis dan serta ilmu berhitung. Pesantren dituntut untuk mampu bersaing dengan sistem pendidikan kontemporer di Indonesia. Tantangan tidak hanya datang dari luar, melainkan juga dari dalam dunia pesantren sendiri. Peran yang sangat kompleks dari seorang Kyai misalnya, memerlukan kajian khusus, dan tulisan ini menelaah tentang sejarah, peran kyai dan kerangka institusional pesantren. Disimpulkan bahwa bahwa perlu adanya penelaahan kembali tentang peran pimpinan pesantren dan pola komunikasi di dalam pesantren dalam rangka merespon persoalan-persoalan kekinian yang mempengaruhi dunia pendidikan di Indonesia, sehingga diperlukan adanya restrukturisasi dan penataan kembali pesantren. Proses restrukturisasi meliputi transformasi peranan pimpinan dan keterlibatan para guru dalam mengembangkan kurikulum belajar mengajar. Sedangkan penataan kembali diantaranya meliputi dikembangkannya rasa tanggung jawab kolektif diantara para guru dan penataan infrastruktur pesantren. Singkatnya, pesantren sebenarnya sudah memiliki potensi dan sumber daya untuk mengakomodir perubahan yang terjadi di masyarakat. Figur kyai menjadi sangat penting untuk menelaah kembali sumberdaya dimaksud. How to Cite : Rahayani, Y. (2017). Restructuring and Redesigning the Pesantren Toward an Effective Educational Institution. TARBIYA: Journal of Education in Muslim Society, 4(2), 114-127. doi:10.15408/tjems.v4i2.8009. Permalink/DOI: http://dx.doi.org/10.15408/tjems.v4i2.8009